Optimization and prioritization of paediatric drugs for visceral leishmaniasis - Masini, Tiziana; Maia-Elkhoury, Ana Nilce Silveira; Mondal, Dinesh; Olliaro, Piero; Paudel, Khechar N.; Penazzato, Martina; Branco Valadas, Samantha Yuri Oshiro; Yajima, Aya; Beshah, Abate; Warusavithana, Supriya; Jain, Saurabh (Frontiers in Pediatrics, 2025)
Visceral leishmaniasis (VL) is a fatal disease if left untreated. Globally, at least 50% of VL cases are reported to be children younger than 15 years, with a higher incidence among males. VL is intrinsically associated with poverty and poor social determinants of health. Malnutrition and immune suppression are risk factors for severe VL, making children particularly vulnerable to this disease. Available treatment options vary depending on the eco-epidemiological context, but are in general suboptimal, especially for children. In 2023, the World Health Organization convened a paediatric drug optimization exercise (PADO) for VL, bringing together more than 60 experts globally in the field of VL to identify formulations of VL medicines to prioritize for development to address the specific needs of children. The group prioritized a 20 mg scored, dispersible tablet formulation of miltefosine and an oral solid dosage form of amphotericin B, acknowledging recent developments in allometric dosing for miltefosine and ongoing research for the development of oral amphotericin B. For miltefosine, this prompted an ongoing update of the WHO Prequalification Expression of interest to promote generic manufacturing. A compound with a new mechanism of action, LXE408, which is currently being investigated in Phase II, was included in the PADO watch list, signalling that paediatric investigations should start as soon as enough data are available from adult studies, not to delay access to latest available innovations for children with VL.